Hippocampal Changes in Down's Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
Semiquantitative scales and quantitative computerized image analyses were used to determine the neurofibrillary tangle formation and AB amyloid deposition in the hippocampal formation and inferior temporal gyrus in 36 Down's syndrome cases, aged 4 to 73 years.